2017
DOI: 10.1093/mnras/stx360
|View full text |Cite
|
Sign up to set email alerts
|

Shaken and stirred: the Milky Way's dark substructures

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
151
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(179 citation statements)
references
References 119 publications
23
151
1
Order By: Relevance
“…Any of these processes may act to blow out gas from the galaxies in our baryonic simulations, shallowing their gravitational potential significantly in lowermass galaxies like dwarfs, which in turn allows for easier removal of dark matter mass through gravitational interactions. Sawala et al (2017) also found that the abundance of for subhalos with masses below 10 9.5 M in the APOSTLE simulations was reduced at all distances out to 200 kpc from the hosts. For the largest distances they examine, between 50 and 200 kpc, Sawala et al (2017) found a reduction in substructure abundance of 23 per cent.…”
Section: Comparison With Dark Matter-only Simulationsmentioning
confidence: 54%
See 1 more Smart Citation
“…Any of these processes may act to blow out gas from the galaxies in our baryonic simulations, shallowing their gravitational potential significantly in lowermass galaxies like dwarfs, which in turn allows for easier removal of dark matter mass through gravitational interactions. Sawala et al (2017) also found that the abundance of for subhalos with masses below 10 9.5 M in the APOSTLE simulations was reduced at all distances out to 200 kpc from the hosts. For the largest distances they examine, between 50 and 200 kpc, Sawala et al (2017) found a reduction in substructure abundance of 23 per cent.…”
Section: Comparison With Dark Matter-only Simulationsmentioning
confidence: 54%
“…Sawala et al (2017) also found that the abundance of for subhalos with masses below 10 9.5 M in the APOSTLE simulations was reduced at all distances out to 200 kpc from the hosts. For the largest distances they examine, between 50 and 200 kpc, Sawala et al (2017) found a reduction in substructure abundance of 23 per cent. This is similar to our baryons given the cosmic baryon fraction ( f b ≡ Ω b /Ω m ) of our baryonic simulations.…”
Section: Comparison With Dark Matter-only Simulationsmentioning
confidence: 54%
“…Finally, it is important to note that our DM limits are subject to potentially large uncertainties. In addition to the already mentioned caveats in the computation of the minimum detection flux (see Section 3.1), 10 there exist important theoretical uncertainties in the N-body simulation predictions, such as the survival probability of the lightest subhalos near the Galactic center [67][68][69], 11 the precise subhalo structural properties, the impact of baryons on the subhalo population [22,70] or the value of the minimum subhalo mass that is adopted to separate between visible and dark satellites [71]. These and other issues that affect the Galactic subhalo population will be addressed elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…This is another indication that it is the radial sub-halo distribution that drives min ∆ rms to lower values, not the presence of actual satellite planes. In this regard it is important to note that the analysed simulations are collision-less, and that the host halos do not contain central galaxy disks, whose tidal effects can result in a depletion of sub-halos in the innermost regions which results in more radially extended sub-halo systems (Garrison-Kimmel et al 2017;Sawala et al 2017). This effect on the distribution of satellite sub-halos is present in the Phat ELVIS sample that includes a central galaxy potential.…”
Section: Plane Thickness Vs Halo Propertiesmentioning
confidence: 99%